The second half [large type] : a novel - Snelling, Lauraine (Center Point Large Print, 2016)
"A heartfelt story of a couple who, when their son becomes missing in action on a military assignment, put their plans for a peaceful retirement on hold to assume guardianship of their young grandchildren"--